ACTIVITIES OF COORDINATORS AT ANDIJAN STATE UNIVERSITY (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Andijan State University, as one of the largest educational institutions of Uzbekistan, implements many initiatives aimed at further developing the academic and social life of students. One of the important parts of these initiatives is the activity of coordinators. Coordinators are established in order to help students working in various fields in the university, increase their social activity and ensure their academic success.